The impact of mouse passaging of Mycobacterium tuberculosis strains prior to virulence testing in the mouse and guinea pig aerosol models. - Paul J Converse; Kathleen D Eisenach; Sue A Theus; Eric L Nuermberger; Sandeep Tyagi; Lan H Ly; Deborah E Geiman; Haidan Guo; Scott T Nolan; Nicole C Akar; Lee G Klinkenberg; Radhika Gupta; et al. (PLoS ONE)
Background It has been hypothesized that the virulence of lab-passaged Mycobacterium tuberculosis and recombinant M. tuberculosis mutants might be reduced due to multiple in vitro passages, and that virulence might be augmented by passage of these strains through mice before quantitative virulence testing in the mouse or guinea pig aerosol models. Methodology/principal findings By testing three M. tuberculosis H37Rv samples, one deletion mutant, and one recent clinical isolate for survival by the quantitative organ CFU counting method in mouse or guinea pig aerosol or intravenous infection models, we could discern no increase in bacterial fitness as a result of passaging of M. tuberculosis strains in mice prior to quantitative virulence testing in two animal models. Surface lipid expression as assessed by neutral red staining and thin-layer chromatography for PDIM analysis also failed to identify virulence correlates. Conclusions/significance These results indicate that animal passaging of M. tuberculosis strains prior to quantitative virulence testing in mouse or guinea pig models does not enhance or restore potency to strains that may have lost virulence due to in vitro passaging. It is critical to verify virulence of parental strains before genetic manipulations are undertaken and comparisons are made.